OPTIMIZATION OF LACCASE PRODUCTION BY CURVULARIA LUNATA USING MAIZE COB AS SUBSTRATE (FUDMA JOURNAL OF SCIENCES, 2021)
Researchers are showing interest in laccase because it is able to degrade several lignocellulosic biomass. It is important to optimize laccase production to achieve higher yield at a lower cost using agricultural wastes. This study was aimed at optimizing the culture conditions for laccase production. Previously isolated and characterized laccase producing Curvularia lunata was collected from the laboratory of Microbiology department, ABU, Zaria. Maize cobs which were used as substrate were collected from Seed Processing Unit of Institute for Agricultural Research, Zaria and the proximate composition of the substrate was determined according to AOAC guideline. The optimum fermentation type for laccase production was determined after which the culture conditions for laccase production were optimized. Laccase activity was determination by guaiacol assay. The proximate compositions of the maize cob were found to be Moisture content (3.18%), Crude protein (2.50%), Crude fat (32.20%), Crude fibre (3.15), Ash content (1.88%) and Carbohydrate content (57.09%). Higher laccase activity was recorded under solid state fermentation compared to submerged fermentation. The optimum culture conditions were found to be inoculum size 3 x 5 mm, pH 5, incubation temperature 30 oC and incubation period of 6 days. The culture conditions for laccase production by Curvularia lunata using maize cob as substrate were optimized
Keywords: laccase, Curvularia lunata, optimum, fermentation, maize cob, production